2015
DOI: 10.1002/cssc.201500540
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalysis using a Wide Range of the Visible Light Spectrum: Hydrogen Evolution from Doped AgGaS2

Abstract: Doping of nickel into AgGaS2 yields a new absorption band, at a wavelength longer than the intrinsic absorption band of the AgGaS2 host. The doped nickel forms an electron donor level in a forbidden band of AgGaS2 . The nickel-doped AgGaS2 with rhodium co-catalyst shows photocatalytic activity for sacrificial H2 evolution under the light of up to 760 nm due to the transition from the electron donor level consisting of Ni(2+) to the conduction band of AgGaS2 . Apparent quantum yields for the sacrificial H2 evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 26 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…With a decrease of the In/(In + Ga) ratio in AIGS nanoparticles from 1.0 to 0.20, their E g values increased linearly from 2.07 to 2.54 eV. This trend agrees with theoretical expectation. It was reported on the basis of the density functional theory that the conduction band minimum of an AgIn (1‑ y ) Ga y S 2 semiconductor was shifted to a higher level (a more negative potential) with an increase in the ratio of Ga to In, accompanied by an increase in E g , because the orbitals of Ga 4s4p and In 5s5p mainly made the conduction band minimum, in which the Ga orbitals formed higher levels than those of the In orbitals, and because the valence band was composed of S 3p and Ag 4d. AIGS@GaS x nanoparticles exhibited a similar linear relation between the E g and the In content in cores.…”
Section: Resultssupporting
confidence: 87%
“…With a decrease of the In/(In + Ga) ratio in AIGS nanoparticles from 1.0 to 0.20, their E g values increased linearly from 2.07 to 2.54 eV. This trend agrees with theoretical expectation. It was reported on the basis of the density functional theory that the conduction band minimum of an AgIn (1‑ y ) Ga y S 2 semiconductor was shifted to a higher level (a more negative potential) with an increase in the ratio of Ga to In, accompanied by an increase in E g , because the orbitals of Ga 4s4p and In 5s5p mainly made the conduction band minimum, in which the Ga orbitals formed higher levels than those of the In orbitals, and because the valence band was composed of S 3p and Ag 4d. AIGS@GaS x nanoparticles exhibited a similar linear relation between the E g and the In content in cores.…”
Section: Resultssupporting
confidence: 87%
“…With theoretical calculations based on density functional theory for AgInSe 2 and AgGaSe 2 , it was reported that the valence bands of both semiconductors were composed of Se 4p and Ag 4d, while the conduction band minimums of AgInSe 2 and AgGaSe 2 were composed of hybrid orbitals of Se 4s4p with In 5s and with Ga 4s, respectively. Considering that the Ga orbitals formed higher levels than those of the In orbitals, , it is reasonably expected that the CBM of an Ag x In y Ga (1‑ y ) Se 2 semiconductor is shifted to a higher level with an increase in the Ga fraction, that is, with a decrease in the y value, while the VBM is not significantly influenced by the y value. Thus, we conclude that the electronic energy structure and the optical property of AIGSe QDs can be controlled by varying their In/Ga ratio, even without changing the particle size.…”
Section: Results and Discussionmentioning
confidence: 99%
“…33,34 Because the TTB structure of these catalysts still remains after the substitution, the valence band levels of these catalysts should be similar. 35 The alkali and alkaline-earth metals were found to affect the conduction band levels in NaTaO 3 ; thus, a larger band gap means a larger conduction band level, which directly dictates the water splitting and CO 2 conversion ability of a material.…”
Section: Resultsmentioning
confidence: 99%
“…The enlarged band gap is due to the substitution of K + and Sr 2+ for Na + . Large band gaps in tantalates have been reported to be beneficial for photocatalytic water splitting and CO 2 conversion by H 2 . , Because the TTB structure of these catalysts still remains after the substitution, the valence band levels of these catalysts should be similar . The alkali and alkaline-earth metals were found to affect the conduction band levels in NaTaO 3 ; thus, a larger band gap means a larger conduction band level, which directly dictates the water splitting and CO 2 conversion ability of a material.…”
Section: Resultsmentioning
confidence: 99%